Lindbergh - Berg, A. Scott (Andrew Scott) (New York : Berkley Books, 1999)
Chronicles the life of Charles Lindbergh and discusses his childhood, his influence and accomplishments in the aviation industry, his child's murder, and his work on creating an artificial heart
Includes bibliographical references (p. [569]-612) and index.
1200
Keywords: Lindbergh, Charles A. (Charles Augustus), 1902-1974.; Air pilots -- United States -- Biography